Fluktuasi Total Padatan Tersuspensi (Total Suspended Solid) dan Kekeruhan di Selat Lombok - Sinaga, Boiris Benet; Suteja, Yulianto; Dharma, I Gusti Bagus Sila (Journal of Marine and Aquatic Sciences; Vol 6 No 2 (2020), 2020)
Total suspended solid is particles or living components (biotics) such as phytoplankton, zooplankton, bacteria, fungi, or dead components (abiotics) such as detritus and solids (sand, mud, and clay) suspended in water.. Total suspended solids are related to turbidity. Therefore, turbidity and total suspended matter can be used as water quality parameters that can determine whether the water conditions are good or not. The Lombok Strait is semi-closed waters that are influenced by local influences such as input from the river. This will certainly affect the total suspended solids found in the Lombok Strait waters. This research was conducted in November 2017. Field sampling was carried out in the Lombok Strait waters at the point of 116 ° 1'18 "BT, 8 ° 34'12" LS. The sampling time is carried out for 1 x 24 hours, starting on November 3 until the November 4, 2017. From the results obtained, TSS on the Lombok Strait Waters has fluctuated. The highest TSS concentration was found at a depth of 0 when the tide conditions were heading to recede. The lowest TSS concentration is obtained when low tide heading to high tide. Turbidity concentration values ??at 5 - 10-meter depths ranged from 0-0.2 NTU. Turbidity and total suspended solids are different in each depth. The vertical pattern of turbidity distribution in this study shows significant results between the surface and bottom of the water. The value of turbidity decreases with increasing depth and time.